Clinical researchEotaxin (CCL11), TARC [thymus and activation-regulated chemokine (CCL17)], MCP-1 (CCL2) and CCR-1, CXCR-1, CXCR-2 expression in dermatitis herpetiformis and bullous pemphigoid - Żebrowska, Agnieszka; Erkiert-Polguj, Anna; Wągrowska-Danilewicz, Małgorzata; Danilewicz, Marian; Pawliczak, Rafał; Sysa-Jędrzejowska, Anna; Waszczykowska, Elżbieta (Archives of Medical Science, 2009)
Introduction: Bullous pemphigoid (BP) and dermatitis herpetiformis (DH) are skin diseases associated with eosinophilc and neutrophilic infiltrations. Although chemokines are critical for the selective attraction and activation of various leukocyte subsets in the inflammatory process, there are few findings concerning the link between chemokines and their receptors and pathogenesis of autoimmune blistering disease. Material and methods: Skin biopsies were taken from 10 patients with DH, 14 with BP and from 10 healthy subjects. The localization and expression of eotaxin, TARC, MCP-1, CCR-1, CXCR-1 and CXCR-2 in skin lesions and perilesional skin were examined by immunohistochemistry. In addition, the serum concentration of selected cytokines was measured by immunoassays method. Results: Expression of eotaxin and TARC was detected in skin biopsies from BP and DH patients both in the epidermis and in inflammatory influx cells of dermis. Expression of MCP-1 was observed in the same areas, hovewer exclusively in specimens for BP patients. Chemokines expression was detected in both perilesional and lesional skin areas but it was much lower in the former one. CCR-1, CXCR-1 and CXCR-2 expression was confirmed in lesional as well as perilesional skin. The expression of the examined chemokines and their receptors was not observed in biopsies from healthy people. Conclusions: Our research leads to the assumption that chemokines may play a role in the activating and recruiting eosinophils and neutrophils and suggest that difference in chemokine expression pattern may contributes to variations of the cellular infiltration and tissue damage in DH and BP patients.